2010
DOI: 10.1590/s0100-204x2010000500007
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade genética em tambaquis (Teleostei: Characidae) de diferentes regiões do Brasil

Abstract: Resumo -O objetivo deste trabalho foi avaliar a diversidade genética em quatro estoques de tambaquis (Colossoma macropomum) de diferentes regiões do Brasil, por meio de marcador RAPD. Foram utilizados 10 iniciadores para analisar 116 indivíduos, coletados de pisciculturas nos municípios de Urupá, RO, Teixeirópolis, RO, Neópolis, SE e Sorriso, MT. Foram encontradas diferenças nas frequências de 67 fragmentos, com um fragmento exclusivo em Sorriso e dois em Neópolis. Observaram-se altos valores de polimorfismo (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
2
5

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 20 publications
2
19
2
5
Order By: Relevance
“…The results partially agree with those reported by Jacometo et al (2010), who found high genetic variability in tambaqui broodstocks from Northern Brazil, but with low intergroup differentiation and genetic distance. Endogamy is one of the main causes of reduced genetic variability and differentiation among broodstock individuals and populations (Taniguchi, 2003).…”
Section: Genetic Structuresupporting
confidence: 92%
See 3 more Smart Citations
“…The results partially agree with those reported by Jacometo et al (2010), who found high genetic variability in tambaqui broodstocks from Northern Brazil, but with low intergroup differentiation and genetic distance. Endogamy is one of the main causes of reduced genetic variability and differentiation among broodstock individuals and populations (Taniguchi, 2003).…”
Section: Genetic Structuresupporting
confidence: 92%
“…According to Nei's (1973) measure of genetic diversity, average heterozygosity of the three broodstocks was 0.336, with the lowest estimate found for Balbina stock (0.283). Similarly, estimates of genetic diversity were close to those described for tambaqui broodstocks analyzed using RAPD markers (Jacometo et al, 2010). Variations in estimated genetic diversity of the samples may be attributed to the history and level of genetic management of the stocks, although this has been scarcely documented.…”
Section: Genetic Diversitysupporting
confidence: 68%
See 2 more Smart Citations
“…Tambaqui is naturally resilient, tolerates low concentrations of dissolved oxygen and is resistant to sudden changes in pH (Aride et al 2007;Silva et al 2007;Dairiki and Silva 2011). About 80% of tambaqui currently commercialized is produced in captivity (Jacometo et al 2010). The production of matrinxã production was of 9,366,203 tons in 20159,366,203 tons in (IBGE 2015.…”
Section: Introductionmentioning
confidence: 99%